Evaluation for agricultural usage with speciation of heavy metals in a municipal sewage sludge - Hanay, Oezge; Hasar, Halil; Kocer, Niluefer Nacar; Aslan, Sibel (Springer, 2008)
This study was carried out to evaluate the agricultural usage of an anaerobically digested sludge in the contents and fractions of heavy metals. Therefore, a sequential extraction scheme according to the BCR's (Community Bureau of Reference) guidelines and total acid digestion were applied to sewage sludge samples. The results of total heavy metal concentrations in sewage sludge showed that the highest total concentrations were Fe, Zn and Mn. When Turkish, Europe and US EPA directives were compared with each other by depending on the use of sludge for agricultural purposes, all the heavy metals determined for this sludge were below the maximum permitted levels, except for Cd. This sludge should not be applied to land due to its high Cd content. The results of heavy metal fractions indicated that some metals (Cd, Mn, Pb, and Fe) distributed mainly in the residual fraction. All fractions of Zn showed no variation. Cu and Cr were most abundant in the oxidizable phase while Ni was in exchangeable phase. Although total content of Ni in the sludge is lower than the maximum levels allowed by all the directives, it tends to be easily moved and dispersed in the environment. Due to its high mobility, the examined sewage sludge may cause phyto-toxicity after its agricultural application.
Keywords: sequential chemical extraction; heavy metals; sewage sludge; community bureau of reference